Efficient Antimony‐Based Solar Cells by Enhanced Charge Transfer. Issue 2 (4th December 2019) - Nie, Riming; Seok, Sang Il
Abstract: The main mechanism of most solar cells is that the light produces photogenerated electrons and holes, which are transferred to the electron transport layer and the hole transport layer (HTL), respectively. Then, these holes and electrons are transported to the anode and cathode, respectively, to generate electric current. Thus, charge transfer is a crucial process to fabricate efficient solar cells. Here, a fast vapor process is developed to fabricate SbSI and SbSI‐interlayered Sb2 S3 solar cells by annealing an Sb2 S3 film and SbI3 powder in an inert gas atmosphere. The charge transfer of the vapor‐processed SbSI solar cells is increased by shortening the path length from SbSI to the HTL. This is achieved by an intimate contact between SbSI and the HTL, which is obtained by optimizing the morphology of SbSI, resulting in a record power conversion efficiency (PCE) of 3.62% in pure SbSI‐based solar cells under standard illumination at 100 mW cm −2 . In addition, the charge transfer of the SbSI‐interlayered Sb2 S3 solar cells is enhanced by increasing the external driving force, an energetically favorable driving force provided by the TiO2 /Sb2 S3 /SbSI/HTM structure, and the best‐performing SbSI‐interlayered Sb2 S3 solar cell exhibits a PCE of 6.08%. Abstract : The charge transfer is enhanced either by shortening the path length from the light harvester to the electron transport layer (ETL) or hole transport layer (HTL), or by increasing the external driving force. A record power conversion efficiency (PCE) of 3.62% in SbSI‐based solar cells is achieved. The SbSI‐interlayered Sb2 S3 solar cells are demonstrated with a PCE of 6.08%.